2008
DOI: 10.2215/cjn.02180508
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Tourism in the United States

Abstract: Conclusions: Tourists had a more complex posttransplantation course with a higher incidence of acute rejection and severe infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
79
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 24 publications
9
79
0
5
Order By: Relevance
“…It is important that accurate data on outcomes of transplants carried out abroad are known so that patients can be counselled about such activity [24,42] . The outcome of recipients of organs through TT is reported to be inferior to those transplanted under ethically more acceptable conditions (Table 2) [5,6,23,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] .…”
Section: Transplant Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…It is important that accurate data on outcomes of transplants carried out abroad are known so that patients can be counselled about such activity [24,42] . The outcome of recipients of organs through TT is reported to be inferior to those transplanted under ethically more acceptable conditions (Table 2) [5,6,23,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] .…”
Section: Transplant Outcomementioning
confidence: 99%
“…Transplants performed in less than ideal circumstances are characterised by inadequate pretransplant evaluation, general lack of information about peri-operative issues, immunosuppression and long term outcome. Despite these factors, there are numerous reports indicating that TT is associated with a high incidence of surgical complications, acute rejection and invasive infection which cause major morbidity and mortality [5,23,25,29,43,44,46,49,50,51,[55][56][57][58] .…”
Section: Transplant Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The negative impact of trafficking of human organs and transplant tourism on the application of transplant technology and the exploitation of the vulnerable people as organ providers has been documented worldwide (Gill et al 2008;BudianiSaberi and Delmonico 2008;WHO 2010). As stated in the Declaration of Istanbul, ''organ trafficking and transplant tourism violate the principles of equity, justice and respect for human dignity, …transplant commercialism targets impoverished and otherwise vulnerable donors, it leads inexorably to inequity and injustice…'' (Steering Committee of the Istanbul Summit.…”
mentioning
confidence: 99%
“…Cosmetic tourism has been described as a 'burden' on the United Kingdom National Health Service due to the requirement for inpatient emergent treatment and corrective or revision surgery [9,10]. Comparing a matched cohort of renal transplant patients from University of California, Los Angeles with renal transplant 'tourists', Gill et al [11] found a more complex post-transplantation course and higher incidence of acute rejection in the tourism cohort. In contrast, Geddes et al and Canales et al [12,13] report a generally good outcome for renal transplantation outside of the country of residence.…”
mentioning
confidence: 99%